Measuring and Assessing Regional Education Inequalities in China under Changing Policy Regimes - Xiang, Lili; Stillwell, John; Burns, Luke; Heppenstall, Alison (Applied spatial analysis and policy, 2020)
China’s uneven regional economic development and decentralisation of its education system have led to increasing regional education disparities. Here, we introduce a new multidimensional index, the Index of Regional Education Advantage (IREA), underpinned by Amartya Sen’s capability approach, to evaluate the effectiveness of policies targeted at reducing regional/provincial educational inequalities in China since 2005. The analysis of the distribution of IREA scores and the decomposition of the index reveals that education in north-eastern China is better than in the south-west part of the country, a pattern which lacks conformity with the eastern, middle and western macro-divisions adopted by Central Government as the basis of policy implementation. In addition, the education of migrant children and the low transfer rate into high schools are identified as key issues requiring Government attention.